Investigating the Influence of Exchange Rate Volatility on Bilateral Trade in China - Qian Wang (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
This paper aims to investigate the influence of exchange rate volatility on China’s bilateral trade with its top five trade partners, namely the United States, Japan, Hong Kong(SAR)China, South Korea, and Germany. The quarterly data covering from 2000 to 2018 is used. This study uses the GJR-GARCH(1,1) model to quantify the exchange rate volatility of the Chinese yuan against the US dollar, Japanese yen, Hong Kong dollar, Korean won, and Euro. Threshold models(STR) are used to explore the impact and threshold effects of exchange rate volatility on China's import and export trade with the United States, Japan, Hong Kong, South Korea, and Germany.The findings suggest that in the import and export models of different countries, the volatility of the RMB exchange rate can influence China’s bilateral trade, and it has different multiple threshold effects on China’s imports and exports. However, the direction and intensity of the impact of RMB exchange rate volatility on China's imports and exports are not exactly the same because of the different values of threshold variables in each specific country's import and export models. Taking the gross domestic product growth and the inflation rate as a reference, the threshold effect of the RMB exchange rate volatility on China with its trade partners is different due to the different economic conditions of eacheconomy